Prototipo de vivienda progresiva con materiales vernáculos, hidrorrepelentes y estrategias bioclimáticas en Mucho Lote 1 – Guayaquil - Laguatasig Ruiz, Juan Manuel (2025)
This thesis presents the design of a progressive housing prototype for the Mucho Lote 1 area in Guayaquil, integrating vernacular materials, hydrophobic treatments, and bioclimatic strategies to enhance habitability and sustainability. Guayaquil faces a significant housing deficit, especially in sectors dominated by informal constructions using industrial materials ill-suited for the local humid tropical climate. The proposed modular progressive design is based on three core units (bathroom, kitchen-dining room, and bedroom), allowing incremental growth aligned with the economic capacity of residents. The study analyzes the physical, social, and natural context of Mucho Lote 1, highlighting climatic, structural, and thermal comfort deficiencies. A mixed-method approach, including community surveys, evaluates the knowledge and willingness to adopt traditional materials and sustainable building techniques. The prototypes incorporate bamboo cane and other native materials treated with hydrophobic substrates, applying bioclimatic principles such as cross ventilation, shading, and leveraging wind and vegetation..........